2006
DOI: 10.1021/pr060100p
|View full text |Cite
|
Sign up to set email alerts
|

Statistical Analysis of the Experimental Variation in the Proteomic Characterization of Human Plasma by Two-Dimensional Difference Gel Electrophoresis

Abstract: The complexity of human plasma presents a number of challenges to the efficient and reproducible proteomic analysis of differential expression in response to disease. Before individual variation and disease-specific protein biomarkers can be identified from human plasma, the experimental variability inherent in the protein separation and detection techniques must be quantified. We report on the variation found in two-dimensional difference gel electrophoresis (2-D DIGE) analysis of human plasma. Eight aliquots… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
46
0
2

Year Published

2007
2007
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 47 publications
(51 citation statements)
references
References 24 publications
3
46
0
2
Order By: Relevance
“…While lys residues are almost ubiquitous in proteins, inter-protein variability can be expected as proteins do not have uniform amino acid content and lower abundance proteins are less likely to be labeled [10,132]. In addition, it has also been reported that gel-to-gel variation still contributes most of the inherent variability to DIGE [144]. It is also important to consider the ramifications of selectively labeling a sample and subsequently loading only a fraction of this sample for electrophoresis; the total complement of detectable protein is thus reduced by the very design of the protocol used for detection.…”
Section: Reactive Fluorescent Dyesmentioning
confidence: 99%
“…While lys residues are almost ubiquitous in proteins, inter-protein variability can be expected as proteins do not have uniform amino acid content and lower abundance proteins are less likely to be labeled [10,132]. In addition, it has also been reported that gel-to-gel variation still contributes most of the inherent variability to DIGE [144]. It is also important to consider the ramifications of selectively labeling a sample and subsequently loading only a fraction of this sample for electrophoresis; the total complement of detectable protein is thus reduced by the very design of the protocol used for detection.…”
Section: Reactive Fluorescent Dyesmentioning
confidence: 99%
“…For example, it is possible to analyze proteomic data using statistical packages [15]. These statistical analysis software packages can result in increased confidence for the differential expression data, but require extensive statistical expertise [16][17][18]. The Extended Data Analysis (EDA) module of DeCyder serves as an alternative analysis tool which can provide multivariate statistics, such as principal component analysis (PCA) [19][20][21][22], hierarchical clustering [23][24][25][26], K-means clustering [27], and biomarker selection [28][29][30], and can be evaluated by scientists with less statistical expertise.…”
Section: Introductionmentioning
confidence: 99%
“…Karp and Lilley [16] noted that a certain spot was much brighter in the Cy5 image than in the Cy3 image. In a recent study of experimental variation in DIGE, Corzett et al [22] employed a linear mixed model, which included a protein-specific dye term. We, therefore, chose to carry out a systematic analysis of dye effects in DIGE.…”
Section: Introductionmentioning
confidence: 99%
“…The dye correcting term in the linear mixed model is the same as the one used in Corzett et al [22] and in the microarray literature [24,30]. The paper by Corzett et al [22] analyzes experimental variation in DIGE experiments and they included the dye term without discussing or showing the necessity of a dye correction.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation